Bone structure, strength and microhardness resulting after hindlimb unloading in rats - Carvalho, Antonio Augusto Ferreira [UNESP]; Louzada, Mário Jefferson Quirino [UNESP]; Nakamune, Ana Cláudia de Melo Stevanato [UNESP] (My University, 2009)
Introduction: Bone strength is influenced by a number of different determinants, such as mass, size, geometry and also by the intrinsic material properties of the tissue. Aims: The structure and mechanical properties of the femur were analyzed in aged (14 mo-old) animals submitted to hindlimb unloading (HU) for 21 days. Methods: Twenty Wistar rats were randomly divided into Control and HU groups and the femur was submitted to dual X ray absorptiometry (DXA), DIGORA radiographic density, mechanical compression testing and Knoop microhardness analyse in cortical and cancellous bone. Results: Femurs from HU group presented significantly lower failure load, decreased bone mineral density (BMD)/bone mineral content (BMC) in whole bone; proximal/distal epiphysis and middiaphyseal cortical bone measured by DXA were similar in the two groups; radiographic density from areas in proximal epiphysis was significantly lower in HU group, and microhardness measured at periosteal and endosteal levels were also signifcantly diminished in HU compared with Control group. Conclusion: Disuse induced damage in the trabecular femoral bone architecture with decisive effect on the head and trochanteric fossa, which became weaker. Bone diaphyseal cortical hardness also suffered effect of unloading, probably related to osteocyte/osteoblast activity.
Keywords: Bone densitometry; Bone microhardness; Mechanical strength; Rat femur